Semiclassical quantization condition for magnetic energy levels of electrons in metals with band-contact lines: Электpонные свойства металлов и сплавов - Mikitik, G. P.; Sharlai, Yu. V. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 1999)
We refine the well-known quantization condition for magnetic energy levels of a semiclassical electron. The refined condition results in the energy shift of the levels when in k space the closed electron orbit links to the band-contact line (i.e., surrounds it). This effect is closely analogous to that of Aharonov-Bohm provided the band-contact line plays the role of the infinitely thin &quotsolenoid&quot with the fixed &quotmagnetic flux&quot. The predicted shift must manifest itself in oscillation phenomena.